MATHEMATICAL MODELS TO DETERMINE OF THIN LAYER DRYING KINETIC OF GINGER SLICES - Akpınar, Ebru; Demirci, Seda (My University, 2018)
In the present work, the effects of some parametric values on the thin layerdrying process of ginger slices were investigated. Drying was done in thelaboratory by using cyclone type convective dryer. The drying airtemperature was varied as 40, 50, 60 and 70 ?C and the air velocity is 0.8, 1.5and 3 m/s. All drying experiments had only falling rate period. The dryingdata were fitted to the twelve mathematical models and performance of thesemodels was investigated by comparing the determination of coefficient (R2),reduced chi-square (?2) and root mean square error (RMSE) between theobserved and predicted moisture ratios. Among these models, drying modeldeveloped by Midilli et al. model showed good agreement with the dataobtained from the experiments. From the Midilli et al. model for ginger slices,R2, ?2and RMSE were determined between 0.99587 and 0.99971, 0.0006156and 0.00003721 and, 0.019792 and 0.005597, respectively. Using regressionanalysis, the relationship between the coefficients of Midilli et al. model withdrying air temperature and velocity was investigated.
Keywords: Matematik; Gıda Bilimi ve Teknolojisi